Body fuel : a guide to good nutrition - Shryer, Donna (New York : Marshall Cavendish Benchmark, 2008)
"Provides a basic, comprehensive introduction to human nutrition, including information on how nutrients fuel the body, with a review of the food pyramid and how to read labels to make healthy food choices"--Provided by publisher
State-of-the-art nutrition -- Digesting the facts -- Nutrient know-how -- The marvelous carb -- Fabulous fiber -- Chewing the fat-but moderately -- Power to the proteins -- Turn up the waterworks -- The vitamin and mineral story -- Exercise your options
Includes bibliographical references and index
Keywords: Nutrition -- Juvenile literature; Food -- Juvenile literature; Metabolism -- Juvenile literature